2009
DOI: 10.1590/s0066-782x2009000300007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e variáveis associadas à inatividade física em indivíduos de alto e baixo nível socioeconômico

Abstract: SummaryBackground: Studies that considered only the leisure physical activity found that the physical inactivity is higher among lower-income individuals. There is a possibility that this association shows modifications, when considering transportation, work and domestic activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
2
1
3
Order By: Relevance
“…This finding is consistent with age differences in MVPA that have been described globally [1,5]. Conversely, while SES is negatively associated with physical inactivity in developed countries [22], the opposite pattern has been observed in Mexican adults in our study and previous Mexican research [20,23]. Thus, Mexican adults within the highest SES group were significantly less likely to engage in recommended levels of MVPA.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with age differences in MVPA that have been described globally [1,5]. Conversely, while SES is negatively associated with physical inactivity in developed countries [22], the opposite pattern has been observed in Mexican adults in our study and previous Mexican research [20,23]. Thus, Mexican adults within the highest SES group were significantly less likely to engage in recommended levels of MVPA.…”
Section: Discussionsupporting
confidence: 91%
“…Matthews 15 mapped the sedentary behaviors of Americans and found that participants spent 54.9% of their time or 7.7 hours / day in sedentary behaviors. The proportion of Brazilian adults who watched TV for three or more hours per day was 28.9% 16 . In addition, in the city of Pelotas (RS), a study found that, on average, adults reported spending 5.8 hours per day in the sitting position.…”
Section: Discussionmentioning
confidence: 99%
“…A nivel latinoamericano, son pocos los estudios que utilizan el IPAQ para medir el nivel de AF de la población, y de estos estudios la mayoría están dirigidos a poblaciones de niños, adolescentes, jóvenes universitarios o adultos mayores, siendo muy escasos los conducidos en población adulta. Un estudio conducido en Brasil, demostró que el NSE alto tenía niveles de inactividad física más elevados que en el NSE bajo 20 , al respecto, en nuestro estudio llama la atención el mayor nivel de actividad física bajo en NSE medio, esto puede deberse a que la medición incluye las actividades relacionadas al trabajo y el transporte, que no fueron consideradas en el estudio brasileño.…”
Section: Discussionunclassified